Differentiation of Innovative Development Strategies of Regions for Improving the Effectiveness of Socio-Economic Policy in the Russian Federation - Sukhovey, Alla F.; Golova, Irina M. (Economy of Regions, 2020)
The study aims to develop a differentiated approach to the elaboration of innovative development strategies of Russian regions, which allows an effective implementation of innovative paradigms, considering the specificity of scientific and technical, innovative, and production and technological potential of regions. The analysis of international experience of innovative development illustrates the need to consider regional features when creating innovative strategies. We examined the dynamics of the innovative potential of Russian regions over the past decade. We hypothesise that an effective targeted innovative strategy of a region should be closely related to its socio-economic strategy, relying on the most relevant scientific, technological, and educational potential. We identified 4 main criteria for differentiating innovative strategies. These criteria application increases the effectiveness of innovation policies. These factors include the relationship of regional innovative strategies with relevant socio-economic strategies, the innovation and technological specialisation of the regions, regional needs for innovative transformations for the future, and forms of innovation activity. A comparative analysis of innovation and production capabilities and needs of Russian regions showed significant differences in the number of people employed in research and development, technological innovation costs, manufacturing output and other indicators. Based on the analysis, we identified top 15 regions, which are the most innovation-ready. The study used comparative analysis methods, economic and statistical methods, and forecasting methods. We proposed an algorithm for using a differentiated approach for strategizing regional innovative development. Finally, we concluded that a differentiated approach to the development and implementation of innovative development strategies allows improving the efficiency and targeting of state innovation policy through more efficient use of available resources and opportunities to strengthen the sustainability of regional communities. The article is intended for experts in the field of theory and practise of managing the innovative development of regions.